Hepatitis B Vaccination: A Historical Overview with a Focus on the Italian Achievements - Luisa Romano’; Alessandro R. Zanetti (Viruses, 2022)
Vaccination is the most effective way to control and prevent acute and chronic hepatitis B, including cirrhosis and HCC, on a global scale. According to WHO recommendations, 190 countries in the world have introduced hepatitis B vaccination into their national childhood immunization programs with an excellent profile of safety, immunogenicity, and effectiveness. Following vaccination, seroprotection rates are close to 100% in healthy children and over 95% in healthy adults. Persistence of anti-HBs is related to the antibody peak achieved after vaccination. The peak is higher the longer the antibody duration is. Loss of anti-HBs does not necessarily mean loss of immunity since most vaccinated individuals retain immune memory for HBsAg and rapidly develop strong anamnestic responses when boosted. Evidence indicates that the duration of protection can persist for at least 35 years after priming. Hence, booster doses of vaccines are currently not recommended to sustain long-term immunity in healthy vaccinated individuals. In Italy, vaccination against hepatitis B is met with success. In 2020, Italy became one of the first countries in Europe to be validated for achieving the WHO regional hepatitis B control targets.